Analisis Sistem Antrean Untuk Optimalisasi Jumlah Server Menggunakan Model Keputusan Tingkat Aspirasi: (Studi Kasus : Restoran Cepat Saji di Samarinda Central Plaza) - Felysia, Novia; Wahyuningsih, Sri; Nasution, Yuki Novia (Program Studi Statistika FMIPA Universitas Mulawarman, 2021)
This research aims to obtain information on the number of cashiers with optimal performance in the fast food restaurant at Samarinda Central Plaza queue system using R Studio software. The queue model applied in this research is (M1/M2/c):(FCFS/∞/∞) with First Come First Served (FCFS) queue discipline. The optimal number of cashiers are determinated by using the aspiration level decision model. The results of the analysis showed that the optimal number of cashiers was 3 cashiers with an average number of customers in the queue as many as 1 customer every 15 minutes, the average number of customers in the queue system as many as 2 customers every 15 minutes, the average waiting time for customers in the queue for 1.2 minutes, the average waiting time of customers in the queue system for 6 minutes, and the percentage of idle time is 2.26% that is about 20.34 seconds